The Biological Activity of Phytochemicals - Gang, David R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
This 41st volume of RAP includes a total of twelve articles, all based on talks presented at the 49th annual meeting of the PSNA. These eight Perspectives and four Communications give a very good picture of the state of plant (bio)chemistry research in North America, which is also indicative of the state of the field worldwide. Each of these articles describes the integration of several different approaches to ask and then answer interesting questions regarding the function of interesting plant metabolites, either in the plant itself or in interactions with the environment (natural setting or human health application). The Phytochemical Society of North America (PSNA) is a nonprofit scientific organization with membership open to those interested in plant biochemistry, phytochemistry, and the role of plant substances in related disciplines. The PSNA exists to encourage and stimulate research in the chemistry and biochemistry of plant constituents, their effects upon plant and animal physiology and pathology, and their industrial importance and utilization. Annual meetings featuring symposium topics of current general interest and contributed papers by conference participants are held throughout Canada, the United States, and Mexico. Information about the PSNA, can be found at www.psna-online.org.
Keywords: Plant ecology; Plant Ecology